A Guarded Courtship: Soviet Cultural Diplomacy in Iran from the Late 1940s to the 1960s. Issue 3 (May 2018) - Mossaki, Nodar; Ravandi-Fadai, Lana
Abstract : By bringing to bear previously unstudied Soviet archival documents and conducting firsthand interviews with former diplomats, the article traces the ways in which the Soviet Union sought out opportunities to reinvigorate deteriorated Soviet‒Iranian ties through cultural organizations and events in Iran during the decades following World War II. A variety of Soviet cultural representatives—from wrestlers to classical musicians to scholars of Iranian literature—were marshaled for this effort, which bore unexpected fruit considering the modest expectations of the Soviet leadership, ideological differences between the two countries, and increasingly dominant US cultural projection. The connections between cultural ties and state goals, Iranian perceptions of Russia, and the Soviet/Russian sympathies of some members of the shah's government are among sub-themes examined.